Análise numérica da flambagem distorcional de perfis formados a frio tipo cartola submetidos à flexão não-uniforme - Dib, Carla de Amorim Lana (2023)
Cold-formed steel (CFS) members stand out among steel structures notably due to their lightness, structural efficiency (high strength-to-weight ratio) and versatility. However, given their thin-walled geometry, CFS are highly susceptible to instability phenomena. The objective of this research is to analyze the structural behavior of cold-formed steel hat-section beams under non-uniform bending about the major and minor-axis, regarding the risks of distortional buckling. Through the Generalized Beam Theory (GBT), using the computational program GBTUL, the geometries where the distortional failure is predominant were selected, presenting: distortional modal participation (Pdist) greater than 85% and distortional critical buckling moments (McrD) significantly below their local (McrD) and global (McrG) counterparts. Through the computational program ABAQUS, a shell finite element model was developed to perform buckling and post-buckling analysis on the selected beams. The results obtained from the developed model – which include equilibrium paths, deformed configurations, failure moments and collapse mechanisms – show that the currently codified Direct Strength Method (DSM) distortional design curve is inadequate to estimate failure moments in the moderate-to-high slenderness range. Thus, modifications in the design curves were proposed, in order to improve the predictions of the beams’ resistant capacity.